Driving the career readiness agenda in Hong Kong higher education - Chan, Benjamin Tak Yuen (Frontiers in Education, 2023)
The concept of "career readiness" can trace its origin to earlier studies about learning and employability in higher education. Policy researchers contend that following the expansion of higher education and subsequent institutional commitment to ensuring student success, the current stage is about emphasizing employability as the primary indicator of graduate outcomes. This policy shift projects the university-employer interface into the spotlight and creates a favorable condition for promoting work-based experiential learning in higher education. While all postsecondary education institutions in Hong Kong give due regard to graduate employment as a measure of successful "university to work transition", most of them however do not offer structured courses to train their students in skills for lifetime employability. This leads to the question of whether the status quo is desirable and what would be an effective lever for effecting change. Should coaching students for career readiness remain the responsibility of career development office or can academic staff can also have a role to play in supporting it? What are the different approaches for teaching about the 'working life' in the crowded undergraduate curriculum space? Answers to the above would depend on how much the higher education sector in Hong Kong is prepared to embark on a "whole-of-life" approach to develop "work conscious" and not just "work ready" graduates. The new direction will help to generate a positive effect on higher education institutions in Hong Kong for them to compete through curricular and pedagogical innovations in support of the career-readiness agenda.